2018
DOI: 10.2147/bctt.s170208
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular aggregated TRPV1 is associated with lower survival in breast cancer patients

Abstract: BackgroundBreast cancer is a malignant disease that represents an important public health burden. The description of new molecular markers can be important to diagnosis, classification, and treatment. Transient receptor potential vanilloid 1 (TRPV1) polymodal channel is expressed in different neoplastic tissues and cell lines of breast cancer and associated with the regulation of tumor growth, tumor neurogenesis, cancer pain, and malignant progression of cancer. In primary and metastatic breast cancer tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Furthermore, the study by Miao et al found highly expressed TRPV1 coupled with better DFS, which was consistent with our finding. However, another article launched by Lozano et al considered that the effect of TRPV1 on cancer survival was not completely dependent on expression quantity but on the distribution pattern [29]. Those researchers defined two patterns: one is the "classical category" that exhibited diffuse expression in whole cells, and the other is the "nonclassical category" that is expressed in aggregates at the ER/Golgi structures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study by Miao et al found highly expressed TRPV1 coupled with better DFS, which was consistent with our finding. However, another article launched by Lozano et al considered that the effect of TRPV1 on cancer survival was not completely dependent on expression quantity but on the distribution pattern [29]. Those researchers defined two patterns: one is the "classical category" that exhibited diffuse expression in whole cells, and the other is the "nonclassical category" that is expressed in aggregates at the ER/Golgi structures.…”
Section: Discussionmentioning
confidence: 99%
“…Other TRP channels seem to have prognostic value. For example, TRPV2 overexpression predicts adverse outcome in patients with esophageal SCC [ 103 ], and TRPM7-positive NPC patients also have worse prognosis than those with TRPM7-negative cancer [ 126 ]. As of today, it is unclear if altered TRP channel expression is the cause or consequence of the disease.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Interestingly, the reverse seems to be true for kidney cancer where TRPV1 is strongly expressed in normal renal tubules with much reduced (or absent) expression in renal cell carcinoma [ 102 ]. Moreover, TRPV1 is a potential negative prognostic marker in breast cancer where TRPV1 expression in the endoplasmic reticulum and Golgi apparatus (and/or the surrounding of these structures) heralds poor prognosis [ 103 ]. It remains to be determined if this observation also holds true for HNSCC ( Table 1 ).…”
Section: Trp Channels As Potential Diagnostic and Prognostic Toolsmentioning
confidence: 99%
“…Reportedly, TRPV1 is expressed in various human cancer tissues [ 21 , 22 , 23 , 24 , 25 , 26 ], with TRPV1 expression found to be associated with lower survival in invasive breast carcinoma [ 27 ]. In melanoma tissues, decreased TRPV1 expression has been observed when compared to normal melanocytes, and TRPV1 overexpression inhibits melanoma growth via Ca 2+ signaling.…”
Section: Discussionmentioning
confidence: 99%